Competence assessment of CMMS for different measuring tasks - Štrbac, Branko; Biševac, Sonja; Hadžistević, Miodrag; Delić, Milan; Acko, Bojan; Havrlišan, Sara (Journal of Production Engineering, 2020)
In order to check the competence of measurement laboratories, there is a need for laboratories to participate in interlaboratory comparisons. Competence of a laboratory is expressed through an En number which compares measurement results and measurement uncertainty of the examined laboratory with measurement results and measurement uncertainty of the reference laboratory. In this research, the design of experiments (DoE) was used for the assessment of measurement uncertainty. Two characteristics of a ring gauge were measured using a coordinate measuring machine (CMM) - diameter and roundness. Experimental investigations were carried out in the Laboratory for Metrology in Novi Sad and the Laboratory for Dimensional Metrology in Maribor, which is the holder of the national standard of the Republic of Slovenia.